Ethynide-stabilized high-nuclearity silver(i) sulfido molecular clusters assembled using organic sulfide precursors. Issue 36 (13th April 2016) - Chen, Zi-Yi; Tam, Dennis Y. S.; Mak, Thomas C. W.
Abstract : Two unprecedented molecular clusters bearing Ag9 S6 @Ag36 and Ag120 S24 cores stabilized by surface ethynide ligands are assembled using novel organic sulfide precursors and structurally characterized by single-crystal X-ray analysis. The figure shows the Ag120 S24 (PhCC)52 core unit of the latter cluster. Abstract : Inexpensive 1, 1′-thiocarbonyldiimidazole and di(2-pyridyl) thionocarbonate have been used as respective sulfide precursors to assemble unprecedented high-nuclearity ethynide-stabilized silver(i ) sulfido molecular clusters [Ag9 S6 @Ag36 (CC t Bu)32 (H2 O)2 ] [Ag(imidazole)(CH3 OH)(H2 O)](BF4 )2 ·8H2 O·2CH3 OH (1 ) and [Ag120 S24 (PhCC)52 Cl4 (2-pyridone)10 (H2 O)8 ](H3 O)4 (SiF6 )8 (BF4 )4 ·CH3 OH·22H2 O (2 ), the latter being the largest isolated silver(i ) ethynide cluster reported to date.